Pentingnya Orang Tua dalam Membantu Perkembangan Keterampilan Membaca Anak Usia Dini - Dwi Setiawan; Lutfi Eskawati; Diana Diana (Jurnal Pengabdian Masyarakat Nusantara, 2021)
This study aims to identify effective methods that parents can use to help young children develop reading skills. Through a literature review and case studies, this research presents various strategies for parents, such as selecting books that match the child’s interests, creating an enjoyable reading environment, and providing positive feedback. The findings are intended to serve as a guide for parents in creating an optimal learning environment for their children. Reading ability is a crucial foundation for cognitive development in children. This study examines the critical role of parents in facilitating the development of reading skills in young children. By reviewing literature, the study highlights various activities that parents can engage in, such as reading together, providing engaging books, and creating a supportive environment for fostering a child’s interest in reading. The findings indicate that active parental involvement in reading activities from an early age has a significant positive impact on improving reading skills, comprehension, and a child's love for books.